Design and Implementation of a Database and RBAC for Scientific and Competency Mapping Web-based Information System for Lecturers at UPN “Veteran” Jawa Timur - Tresna Maulana Fahrudin; Achmad Yusuf Al Makruf (Nusantara Science and Technology Proceedings, 2023)
Scientific and competency mapping web-based information system aims to address several relevant issues within the context of the Tri Dharma framework in higher education, specifically at UPN "Veteran" Jawa Timur. One of the primary issues is how to review and evaluate the implementation of Tri Dharma, especially in the areas of Education and Teaching, Research, Community Service, and publications, in alignment with the parent-subfields of study and competencies mapping in each study program. Therefore, the research proposes to create an innovative solution that can review and evaluate the alignment of implementation of Tri Dharma in higher education. The research developed a database and Role Base Access Control (RBAC) for web-based information system that lecturers can input education and teaching, research, community service activities, and publications based on the available academic fields, while also helping to identify lecturer expertise according to the knowledge mapping in their respective study programs through a visualization dashboard. The development plan for this application begins with the planning phase, including analyze the system's business processes to understand the system needs of users, designing the necessary features, completing master data such as a list of parent field of study and subfield of study for each study program. This is essential for obtaining an initial understanding of the data structure for the database design. After the database design has been completed, the next step is to implement the database design into an actual database structure using MySQL and then proceed with the development of the web-based application. The system was designed to generate curriculum vitae and visualization in the spider chart to make it easier for the user to understand their scientific and competencies.